DYNAMICAL CHAOS IN 6 ï† -RAYLEIGH OSCILLATOR WITH THREE WELLS DRIVEN AN AMPLITUDE MODULATED FORCE. - Amer, Y A; Ahmed, S M; Dahshan, ManarM; Al, N M (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Chaotic behavior of6 ï† -Rayleigh oscillator with three wells is investigated. The method of multiple scale method is used to solve the system up to 3rd order approximation. Effect of parameters is studied numerically; all resonance cases are studied numerically to obtain the worst case. Stability of the system is investigated using both phase